DIVERSE eppur VICINE Associazioni e imprese per la responsabilità sociale - SOLITO, LAURA (Strumenti per la didattica e la ricerca, 2013)
In the broader scenario of social communication, the volume deals with the issue of the communication of social responsibilities: a field which, in recent years, has been offering interesting examples of how it is possible to reconcile corporate values and goals with ethical purposes and values in Italy. Starting from the analysis of some projects carried out by companies and associations in the Italian context, the authors analyse the ways in which people build, manage and renew a relationship between apparently distant and yet close subjects.